2012
DOI: 10.1111/cbdd.12063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Molecular Dynamics and Calculated Binding Free Energies for Nine FDA‐Approved HIV‐1 PR Drugs Against Subtype B and C‐SA HIV PR

Abstract: We report the first account of a comparative analysis of the binding affinities of nine FDA-approved drugs against subtype B as well as the South African subtype C HIV PR (C-SA). A standardized protocol was used to generate the inhibitor/C-SA PR complexes with the relative positions of the inhibitors taken from the corresponding X-ray structures for subtype B complexes. The dynamics and stability of these complexes were investigated using molecular dynamics calculations. Average relative binding free energies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 69 publications
4
41
0
Order By: Relevance
“…A Q7K point mutation was introduced in the protease sequences by site-directed mutagenesis using the QuikChange Ò method (Stratagene, La Jolla, CA, USA) to reduce protease autocatalysis [57]. Expression and purification of the proteases were performed as previously described [6]. Briefly, transformed cells were induced to over-express the proteases as inclusion bodies using isopropyl-b-D-thiogalactopyranoside [58].…”
Section: Expression and Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…A Q7K point mutation was introduced in the protease sequences by site-directed mutagenesis using the QuikChange Ò method (Stratagene, La Jolla, CA, USA) to reduce protease autocatalysis [57]. Expression and purification of the proteases were performed as previously described [6]. Briefly, transformed cells were induced to over-express the proteases as inclusion bodies using isopropyl-b-D-thiogalactopyranoside [58].…”
Section: Expression and Purificationmentioning
confidence: 99%
“…Only recently has the crystal structure of the C-SA protease been elucidated [6], whereas the structure of the subtype B protease has been well studied. Structural comparison of the proteases does not definitively provide a clear basis for the differences in drug binding.…”
Section: Introductionmentioning
confidence: 99%
“…Even though this subtype comprises 70% of the global HIV infection to date, very little experimental and computational work on the C‐SA protease has been reported. Publications investigating the impact of active site mutations on binding energies in the C‐SA protease and the inhibition thereof by pentacycloundecane lactam peptides and peptoids make up a substantial proportion of literature on C‐SA protease.…”
mentioning
confidence: 99%
“…This study employed a similar approach that was previously reported for the wild‐type C‐SA protease . The I36T↑T protease consists of 100 amino acids in each chain; the mutations and insertion are indicated in Figure .…”
mentioning
confidence: 99%
See 1 more Smart Citation